Motivation and consumer behaviour in the context of loyalty programs - Klára Mrkosová; Ondřej Dufek; Luděk Majer (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2012)
The paper introduces the partial results of the marketing research on loyalty programs. The aim was to identify the reasons that lead consumers to participate in loyalty programs and the benefits that are the main motivators for participation in the loyalty program. Respondents had the opportunity to create a loyalty program as they wish. The aim of this paper was also to prove the popularity of loyalty programs based on the principles of the deferred compensation.